The Use of Article 378 of the Criminal Code against Violations of Article 43 Paragraph 2 of the Flats Law on Legal Certainty of Land Ownership Status - Dzulkarnain Alghafuru Syahputra; Bambang Sugiri; Milda Istiqomah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The developer of the apartment is allowed to sell the apartment unit that has not been completed after fulfilling the requirements and obligations as regulated in Article 43 paragraph (2) of the Flats Law. This study aims to analyze and find the accuracy of using Article 378 of the Criminal Code to adjudicate violations of Article 43 paragraph (2) of the Flats Law related to the certainty of land ownership status as the basis for making PPJB and criminal responsibility for notaries against the occurrence of criminal acts in the deed he made related to with the principle of prudence of a notary in carrying out his office. The research method used in this study is normative juridical law research, the approach method used is the statutory regulation approach and the conceptual approach as well as the case approach. From the results of the research and discussion, it can be concluded first: the use of Article 378 of the Criminal Code which is applied to violations of Article 43 paragraph (2) of the Flats Law is inappropriate. The appropriate article for the violation is Article 110 of the Flats Law. Second: For criminal acts that are contained in a notary deed, it can cause the notary to be held criminally responsible for participating in helping the occurrence of a crime.